Persistent lymphopenia in septic patients at Dr. Sardjito General Hospital, Yogyakarta - Doni Priambodo; Rizka Humardewayanti Asdie; Yanri Wijayanti Subronto; Juvita Kurniawan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Sepsis triggers immune responseboth pro-inflammatory and anti-inflammatory. Lymphocytes play an important role in the regulation of the inflammatory response. The decrease in lymphocyte numbers due to continuous apoptosis by sepsiscan suppress the immune system and failure to resolve inflammation. Persistent lymphopenia is also associated with a poor prognosis of sepsis. Currently, there are limited studies about persistent lymphopenia in sepsis patients in low- and middle-income countries, including Indonesia. This study aimed to describe the sociodemographic, clinical, and laboratory patterns of sepsis patients with persistent lymphopenia. This was a descriptive study that analyzed patients’ medical records who were treated at the Department of Internal Medicine, Dr. Sardjito General Hospital, Yogyakarta from January 1st, 2016, to December 31th, 2017. Patients diagnosed with clinical sepsis and persistent lymphopenia were included in the study. The status of persistent lymphopenia was described as lymphocyte counts that remained low or lower (<1.62x103/L) on day 4± 24 h compared to the initial value at the time of sepsis diagnosis (day one). Information of patients’ individual and clinical characteristics, complete blood cell count profiles and culture results were included. The outcomes of interest were the survival status and length of stay of the patients. A total of 101 patients with sepsis and persistent lymphopenia were involved in this study. The average increase in lymphocyte numbers was 73.63 ± 426.86/µL. The main source of infection was pulmonary infection, with a mortality rate of 43.6% and a median survival of 19 days. The average length of stay was 13.1±6.8. Persistent lymphopenia in patients with sepsis has a high mortality. Further research is needed to determine the clinical ramifications of persistent lymphopenia.